Clinical reversal of drug resistance - Goldstein, Lori J. (Current problems in cancer, 1995)
Although combination chemotherapy has had a significant impact on survival for malignancies such as Hodgkin's disease, testicular cancer, and childhood acute leukemias, the majority of cancers are either initially resistant to chemotherapy (renal, colon, ect.) or are initially chemosensitive but acquire resistance during treatment, such as lymphoma and breast cancer. Resistance to chemotherapy remains an obstacle to the successful treatment of human cancer and has been the subject of numerous investigations aimed at identifying the molecular mechanisms of resistance in cancer cells. An improved understanding of the mechanisms by which tumor cells develop resistance to chemotherapy may not only enhance the activity of cytotoxic therapy in advanced malignancies but may ultimately improve the impact of adjuvant therapy, potentially resulting in prolonging disease-free intervals and survival. In this review, therefore, we discuss our current understanding of the MDR1 gene, encoding P-glycoprotein, which is responsible for one mechanism of multidrug resistance (MDR). We also review the evidence supporting the clinical relevance of the MDR1 gene and clinical trials aimed at reversing MDR-mediated resistance. Although MDR-mediated drug resistance has been well characterized in preclinical models, its role in clinical drug resistance is not as well characterized and requires further investigation. Prospective studies are necessary to establish the role of MDR1 gene expression in the clinical resistance. The ability to identify tumors with increased MDR1 gene expression has several potential applications (for example, the prediction of response to chemotherapy and the design of studies aimed at reversal of resistance with agents that inhibit MDR-mediated drug efflux). The initial goal of such trials is to demonstrate the ability to reverse MDR1-mediated drug resistance in the appropriate advanced refractory malignancies. Ultimately, it will be important to incorporate these reversal strategies in the treatment of early-stage disease, at which time the tumor burden is smaller and fewer mechanisms of resistance may be present. Prospective phase I, II, and III clinical trials using reversing agents in conjunction with chemotherapy in malignancies that express the MDR1 gene, such as the hematologic malignancies and breast cancer, are necessary before routine use of agents such as verapamil, quinidine, and cyclosporine, which carry innate toxicities. MDR is a mechanism of drug resistance that provides the potential for an alteration in drug efflux, which may have a significant impact on response and possibly result in improved survival for some cancer, patients.